Pengaruh Budaya Organisasi Sekolah Terhadap Kinerja Guru SMA Negeri di Kota Mataram - Prayoga, Sugeng; Yuniati, Safrida (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2019)
The aimed of this study was to determine the effect of school organizational culture on the performance of teachers of public high schools in the city of Mataram. This research is a quantitative research with ex-post facto method. The population of this study were all teachers of SMA 1 and SMA 5 Mataram, totaling 137. The study sample consisted of 58 teachers taken by probability sampling techniques. The instrument of this study used a questionnaire. The data analysis technique in this study used statistical analysis namely simple regression test and multiple regression. The results of this study are that organizational culture has a positive effect on teacher performance of Public High Schools in Mataram City by 55.2%. Thus, it can be concluded that the better the school’s organizational culture, the performance of teachers in public high schools in the city of Mataram will increase.